IbM Workshop Metode Matematika Gasing Bagi Guru SD Muhammadiyah Se Jakarta Timur - Mulyawati, Ima; Sarwinda, Wiratamasari (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2021)
Abstrak IbM pengabdian masyarakat melalui workshop metode matematika GASING bagi guru SD Muhammadiyah se Jakarta Timur. Tujuan dalam pengabdian ini adalah 1) peningkatan pemahaman tentang penjumlahan dan pengurangan; 2) peningkatan pemahaman tentang perkalian dan pembagian. Penerapan metode GASING dilaksanakan melalui empat tahapan. Tahap pertama adalah tahap persiapan, meliputi pembuatan buku modul, persiapan bahan ajar, workshett, persiapan strategi mengajar, dan koordinasi dengan pihak mitra terkait persiapan workshop. Tahap kedua adalah tahap pelaksanaan workshop, tahap ini diawali dengan pemberian pretest kepada para peserta, dilanjutkan dengan workshop metode matematika GASING, kemudian diakhiri dengan tahap posttest dan tahap pengisian angket kepuasan oleh peserta. Hasil yang dicapai dari kegiatan pengabdian masyarakat adalah pelatihan metode GASING dapat meningkatkan kemampuan guru-guru SD Muhammadiyah se Jakarta Timur dalam menghitung penjumlahan, pengurangan, perkalian. Kata kunci: Motede Matematika GASING, Workshop Matematika GASING SD. IbM Workshop on Gasing Mathematics Method for Teachers of Muhammadiyah Elementary Schools in East Jakarta Abstract IbM community service through a workshop on GASING mathematics methods for Muhammadiyah elementary school teachers in East Jakarta. Aim in this service are 1) increasing understanding of addition and subtraction; 2) increasing understanding of multiplication and division. The application of the GASING method is carried out through four stages. The first stage is the preparation stage, which includes the making of a module book, preparation of teaching materials, worksheets, preparation of teaching strategies, and coordination with partners regarding preparation of workshops. The second stage is the implementation phase of the workshop, this stage begins with giving a pretest to the participants, followed by a workshop on mathematical methods GASING, then ends with the posttest stage and the stage of filling the satisfaction questionnaire by the participants. The result of community service activities is that the GASING method training can improve the ability of East Jakarta Muhammadiyah elementary school teachers to calculate addition, subtraction, multiplicatio. Keywords: GASING Mathematical Methods, GASING Elementary Mathematics Workshop.